2018
DOI: 10.20944/preprints201807.0218.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

State of the Art of Automated Buses

Abstract: Urban transportation in the next few decades will shift worldwide towards electrification and automation, with the final aim of increasing energy efficiency and safety for passengers. Such a big change requires strong collaboration and efforts among public administration, research and stakeholders in developing, testing and promoting these technologies in the public transportation. Working in this direction, in the present work the impact of the introduction of driverless electric minibuses, for the first and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 0 publications
0
26
0
1
Order By: Relevance
“…A possible path to mitigate this scenario is the integration of AVs in the public transport system. Recent projects in the European Union have successfully tested autonomous transit in 7 European cities, carrying more than 60,000 passengers and sharing the infrastructure with other road users (2). Other types of public transit, such as bus rapid transit (BRT) using autonomous platooning with precision docking, will produce a BRT-type service that can offer the same capacity and service as rail transit with significantly less cost (43).…”
Section: Impact On Public Transportationmentioning
confidence: 99%
“…A possible path to mitigate this scenario is the integration of AVs in the public transport system. Recent projects in the European Union have successfully tested autonomous transit in 7 European cities, carrying more than 60,000 passengers and sharing the infrastructure with other road users (2). Other types of public transit, such as bus rapid transit (BRT) using autonomous platooning with precision docking, will produce a BRT-type service that can offer the same capacity and service as rail transit with significantly less cost (43).…”
Section: Impact On Public Transportationmentioning
confidence: 99%
“…Even if dozens of trials of autonomous shuttle busses have been carried out, there are a few previous studies on it [20]. Results from the trial in Berlin-Schöneberg, Germany indicated that the acceptance and use of autonomous vehicles in public transport is influenced by their perceived usefulness, ease of use, and social influence [21].…”
Section: Introductionmentioning
confidence: 99%
“…Autonomous vehicles have typically been researched from the point of view of technology, operating environmentally and even other road users such as pedestrians [20,23,24] or estimating travel behaviour implications via a naturalistic experiment [25]. In this research, we focus on real-life experiences, perceptions, and feelings of passengers travelling in driverless shuttle bus in Espoo, Finland.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, autonomous buses constitute a topic that has been barely addressed in the literature [12]. The few existing studies are generally focused on psychological barriers [9,10], while this paper offers a more holistic approach.…”
Section: Discussion Of Resultsmentioning
confidence: 98%
“…The barriers that are required to be overcome in order to introduce autonomous vehicles to the road and the consequences of this development are uncertain, and several researchers have analyzed this previously [2,4,8]. The positive and negative aspects of these reported technologies from these studies-and in certain others conducted on autonomous buses [9][10][11], a topic for which the literature is scarce [12]-are summarized in Table 1. Table 1.…”
Section: Introductionmentioning
confidence: 99%